The influence of perceived values on intentions to use halal cosmetics among engineering students at Universitas Muhammadiyah Yogyakarta: partial least squares-structural equation modeling - Octavia, Mega; Septiana, Chantika Altian; Huriyah, Titih; Permana, Iman (Universitas Ahmad Dahlan, 2025)
The Ministry of Industry of the Republic of Indonesia has emphasized the importance of cosmetics as an essential need due to the increasing awareness of the general population. Various values, including functional, conditional, emotional, social, epistemic, and religious, influence individuals in selecting cosmetics, particularly halal cosmetics, given Indonesia's predominantly Muslim population. This study aims to identify the factors influencing the adoption of halal cosmetics among students of the Faculty of Engineering at Muhammadiyah University of Yogyakarta. This research employs a non-experimental quantitative design using a survey method with a cross-sectional approach and a questionnaire as the primary instrument. The sample consists of 137 students who use halal cosmetics, selected through purposive sampling based on inclusion criteria, namely active students who have used or are currently using halal cosmetics. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The PLS-SEM analysis revealed that functional, conditional, emotional, and epistemic values have a positive and statistically significant influence on the usage of halal cosmetics, with p-values of 0.089, 0.001, 0.001, and 0.004, respectively. In contrast, social and religious values showed no significant relationship with halal cosmetics usage, with p-values of 0.706 and 0.374, respectively. Therefore, this study concludes that the adoption of halal cosmetics among students of the Faculty of Engineering at Muhammadiyah University of Yogyakarta is primarily driven by functional, conditional, emotional, and epistemic values rather than social or religious values.